2002
DOI: 10.1021/ic0112692
|View full text |Cite
|
Sign up to set email alerts
|

Solution and Solid State Studies of a Triangle−Square Equilibrium:  Anion-Induced Selective Crystallization in Supramolecular Self-Assembly

Abstract: We report that an equilibrium mixture of triangular and square supramolecular species results when the flexible, ditopic donor unit, trans-bis(4-pyridyl)ethylene, is reacted with the ditopic acceptor unit, cis-(Me(3)P)(2)Pt(OTf)(2), in a one-to-one ratio. Both products are characterized in solution, by way of multinuclear NMR, and in the solid state, via X-ray crystallography. The effects of water and anions, cobalticarborane versus triflate, on the equilibrium are probed. The selective crystallization of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(102 citation statements)
references
References 19 publications
(15 reference statements)
9
89
1
3
Order By: Relevance
“…Another example of anion-induced crystallization was recently reported by Stang et al [38] While studying the triangle-square equilibrium shown in Scheme 19, it was found that the selective crystallization of each one of the two metallapolygons can be selectively achieved by the appropriate choice of solvents and ratio of anions. In acetonitrile a mixture of the square 30 (11 %) and the triangle [38] Figure 12.…”
Section: Anion-directed Crystallization Of Supramolecular Assembliesmentioning
confidence: 90%
See 1 more Smart Citation
“…Another example of anion-induced crystallization was recently reported by Stang et al [38] While studying the triangle-square equilibrium shown in Scheme 19, it was found that the selective crystallization of each one of the two metallapolygons can be selectively achieved by the appropriate choice of solvents and ratio of anions. In acetonitrile a mixture of the square 30 (11 %) and the triangle [38] Figure 12.…”
Section: Anion-directed Crystallization Of Supramolecular Assembliesmentioning
confidence: 90%
“…These two systems described by Stoddart et al [37] and by Stang et al [38] demonstrate the importance of anions in inducing selective crystallization of a specific supramolecular assembly. They also point out that the solid-state structure of a thermodynamically controlled system does not necessarily have to be the same than that one present in solution.…”
Section: Anion-directed Processesmentioning
confidence: 91%
“…For example, the combination of Pt(PMe 3 ) 2 corner units with 1,2-bis(4-pyridyl)ethylene (bpe) has generated a triangular structure, [{Pt(PMe 3 ) 2 } 3 (bpe) 3 ] 6+ (Fig. 2a) [7], while Pd(en) units (en ¼ ethylenediamine) and 4,4 0 -bipyridine (bipy) gave a cationic square [{Pd(en)} 4 (bipy) 4 ]…”
Section: Inorganic Metalla-assembliesmentioning
confidence: 99%
“…4a). These chiral hosts possess a small hydrophobic cavity 6+ (a) [7] and [{Pd(en)} 4 (bipy) 4 ] 8+ (b) [8] Drug Delivery by Water-Soluble Organometallic Cagescapable of accommodating cationic or neutral guest molecules [12]. Using metal-metal paddlewheel units, Cotton and Murillo have prepared several twoand three-dimensional inorganic assemblies [14].…”
Section: +mentioning
confidence: 99%
“…4) [33]. The existence of square/triangle equilibria for certain combinations of linear and 90 precursors has also provided evidence for [3+3] triangles, wherein distortions in the building blocks relax the encoded angularities [31,[34][35][36]. In some cases, despite the use of cis-capped square planar metal environments, triangles may still be obtained provided that the ligand can accommodate the necessary distortions [37], as when mixing (en)PtCl 2 with 2,2 0 -bipyrazine in the presence of AgNO 3 [38], or by linking the luminescent Pt(thpy)(Hthpy)Cl or [nBu 4 N][Pt(bzqn)Cl 2 precursors with sodium benzimidazolate, thereby cyclizing a 90 acceptor with a 150 donor [39].…”
Section: Triangles Hexagons and Other 2d Metallacyclesmentioning
confidence: 99%